Experimental assessment of the flexural behaviour of concrete-filled steel tubular beams with octagonal sections. (15th November 2019) - Chen, Junbo; Chan, Tak-Ming
Highlights: Eight CFST beams with octagonal cross-section were tested. Three concrete grades were considered in the test programme. The test results revealed ductile behaviour of the specimens. Test results were compared with different design provisions. Strength and stiffness deteriorations of the specimens were discussed. Abstract: This paper presents an experimental investigation into concrete-filled steel tubular beams with octagonal cross-sections (OCFST) under monotonic or cyclic flexural loading. A total of eight tests, including four cyclic specimens and four monotonic counterparts, were conducted. Three concrete grades with measured compressive cylinder strength ( f c ′) varying from 54.5 MPa to 105.6 MPa were used to infill the OCFST specimens. The failure modes, ultimate bending moments, effective flexural stiffness, cumulative dissipated energy and deteriorations of test specimens were discussed. Test results indicate that OCFST beams exhibit a ductile plastic mode and excellent energy dissipation. Concrete grades seem to have limited influence on the ultimate strength and energy dissipation capacity. The comparison results of the ultimate bending moments and effective flexural stiffness between predictions using EN 1994-1-1 and AISC 360-16 and test results reveal their applicability to the design of OCFST beams. An energy-based hysteretic rule was adopted to assess the strength and stiffness deteriorations of the OCFST beams, and the results indicate that the predictions match well with the test observations.